2021
DOI: 10.1371/journal.pone.0251029
|View full text |Cite
|
Sign up to set email alerts
|

Clinical judgment model-based nursing simulation scenario for patients with upper gastrointestinal bleeding: A mixed methods study

Abstract: Assisting patients with upper gastrointestinal bleeding is a crucial role for nurses, and as future nurses, students should demonstrate sound clinical judgment. Well-structured, high-quality simulations are useful alternatives to prepare students for clinical practice. However, nursing simulation scenarios focused on enhancing clinical judgment in managing upper gastrointestinal bleeding are limited. This study aims to develop, apply, and evaluate an effective nursing simulation scenario for patients with uppe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 25 publications
0
11
0
1
Order By: Relevance
“…One of the concepts that emerged in the findings of this study, and that has been repeated continuously throughout simulation learning research, is that students appreciate a learning opportunity that poses no risk to human life. 2 Students feel that simulation learning prepares them for the work they will be doing after graduation, and it enables them to practise rare skills that they would not easily have been able to do in a real clinical setting. 20 Our findings also echo previous research which found that simulation learning improves student confidence.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…One of the concepts that emerged in the findings of this study, and that has been repeated continuously throughout simulation learning research, is that students appreciate a learning opportunity that poses no risk to human life. 2 Students feel that simulation learning prepares them for the work they will be doing after graduation, and it enables them to practise rare skills that they would not easily have been able to do in a real clinical setting. 20 Our findings also echo previous research which found that simulation learning improves student confidence.…”
Section: Discussionmentioning
confidence: 99%
“…2 When teaching the skills that are needed in any Emergency Medical Care (EMC) course, such as critical thinking, clinical reasoning and patient management, simulation has been found to be an effective educational approach. 3 It should be noted that simulated clinical scenarios are critical in the developmental process of a student's treatment plans and clinical thinking 2 and play an important role in bridging the gap between theory and clinical practice. 4 The use of simulation in paramedic, nursing and medical doctor training has proven to have a positive effect on patient safety.…”
Section: Introductionmentioning
confidence: 99%
“…Hanley et al [14] used three concepts of Tanner's Model of Noticing, Interpreting, and Responding in clinical practice in their quality improvement process to improve patient safety by teaching the nurses how to operationalize in clinical practice. [15] Tanner's clinical judgment model in a high-fidelity simulation scenario for undergraduate nursing students to manage a patient with gastrointestinal bleeding. The result showed a significant increase in the students' theoretical knowledge, clinical performance skills, and self-confidence [15].…”
Section: Theoretical Frameworkmentioning
confidence: 99%
“…[15] Tanner's clinical judgment model in a high-fidelity simulation scenario for undergraduate nursing students to manage a patient with gastrointestinal bleeding. The result showed a significant increase in the students' theoretical knowledge, clinical performance skills, and self-confidence [15].…”
Section: Theoretical Frameworkmentioning
confidence: 99%
See 1 more Smart Citation